Discriminant Analysis of IT Employees’ Performance - Jeeva Kumar, S; Muthu, C (International Journal of Computer Sciences and Engineering, 2025)
Several business problems have many possible solutions across many variables. The multivariate techniques, such as Discriminant Analysis, are often used for solving such business problems. In this Paper, the Discriminant Analysis Technique is used to generate a set of well-defined rules, which would be very helpful to the HR department of an IT Company at the time of new recruits.